Investigation of Laplace barriers for arrayed electrowetting lab-on-a-chip - Schultz, A (Langmuir : the ACS journal of surfaces and colloids, 2014)
Partial-post Laplace barriers have been postulated as a means to allow electrowetting transport and geometrical reshaping of fluids, followed by the preservation of fluid geometry after the electrowetting voltage is removed. Reported here is the first investigation of Laplace barriers with the arrayed electrodes and splitting/merging transport functions for an electrowetting lab-on-a-chip. Laplace barriers optimized for 500 × 500 μm(2) electrodes and 78 μm channel height are shown to provide geometrical control of fluid shape down to radii of curvature of ~70 μm. The Laplace barriers increase the splitting volume error, but with proper electrical control, the average error in the split volume is reduced to 5%. Improved programmable fluid storage in droplets or reservoirs and continuous channel flow are also shown. This work confirms the potential benefits of Laplace barriers for lab-on-a-chip and also reveals the unique challenges and operation requirements for Laplace barriers in lab-on-a-chip applications